Youth Voice, Economic Growth and Gen Z Empowerment in Lumbini Province - KC, Nahakul (LTU Journal of Advanced Computing & Engineering, 2026)
Lumbini Province of Nepal faces a dual challenge of harnessing the demographic dividend of a large youth population while addressing persistent youth unemployment and outward labor migration. Drawing on the FY 2082/83 provincial budget priorities and recent policy initiatives, this paper examines how structured youth voice and policy dialogue can strengthen economic governance and youth-responsive development outcomes. It situates youth employment, entrepreneurship, and digital economy opportunities within the province’s broader growth strategy and highlights the role of institutionalized dialogue mechanisms linking young people with provincial decision-makers. The paper also reflects on the contribution of development partners, particularly the UK’s Foreign, Commonwealth and Development Office (FCDO) through the British Embassy Kathmandu and The Asia Foundation (TAF), in advancing collaborative governance and evidence-based policymaking at the subnational level. The paper concludes with policy recommendations aimed at translating youth participation into tangible economic outcomes in federal Nepal.